Kajian Tingkat Akurasi Sensor pada Rancang Bangun Alat Ukur Total Dissolved Solids (TDS) dan Tingkat Kekeruhan Air - Wirman, Rahmi Putri; Wardhana, Indrawata; Isnaini, Vandri Ahmad (Jurnal Fisika, 2019)
Total Dissolved Solids (TDS) and turbidity of water are parameters to determine the quality of water. In this research, instruments development and study of accuracy level for TDS meter and turbidimeter have been made. Instruments were made using TDS sensor and turbidity sensor that were inexpensive and available on the market. The samples used for instruments examination were water with dye (Rhodamine B) and powder of coffee as impurities. The results showed that the sensors worked properly and provided a better accuracy in measuring water samples with coffee impurities than dye impurities. The inaccuracy on the determination of water samples with dye impurities due to dye particles which have soluble properties on water and microscopic size than particles of coffee.